Exposição aguda a baixa concentração de cloreto de mercúrio induz disfunção endotelial em aorta de ratos - Lemos, Núbia Belem (2009)
The toxic effects of mercury and its derivatives vary extremely involving effects from the reproductive until the neural cells, the last ones being very well known. However, its action on the vascular system, at small concentrations, similar to the ones found in the blood after occupational exposure, are not completely elucidated yet. Therefore, this study was performed to study the effects for 45 min of acute administration of 6 nM HgCl2 on the vascular reactivity. Isolated aortic rings from Wistar rats (200- 300 g) were used to investigated the vascular reactivity to phenylephrine in the absence (control) and presence of 6 nM HgCl2. Vascular reactivity to phenylephrine (10-10 to 3.10-4 M) was evaluated in the presence (E+) and absence (E-) of endothelium. To investigate putative factors involved in HgCl2 actions concentration-response curves to phenylephrine were performed with and without HgCl2 with 100 µM L-NAME, 10 µM losartan, 10 µM enalapril, 10 µM indometacine, superóxide dismutase (SOD, 150 U/ml) and apocinine (Apo, 100 mM). Endothelial integrity was evaluated with the acetylcholine (ACh, 10-10 _ 3.10-4 M) induced relaxation and the smooth muscle integrity with the relaxation produced by sodium nitroprusside (NPS, 10-11 - 3.10-7 M) in rings precontracted with 10-6 M phenylephrine. HgCl2 increased the maximal response (Rmax – control: 93,5 ± 2,5 vs HgCl2: 117 ± 3,4 %) and sensitivity to phenylephrine (pD2– control: -6,47 ± 0,08 vs HgCl2: -6,77 ± 0,1 M). This increment was abolished after endothelial damage. L-NAME administration increased Rmáx and pD2 of phenylephrine reactivity both in the presence and absence of HgCl2.The magnitude of this effect (evaluated by dAUC) was reduced in the presence of HgCl2 (dAUC% - control: 134 ± 22 vs HgCl2 64,89 ± 11%). The vasodilatation induced by Ach and NPS was not changed after HgCl2 administration. However, losartan and enalapril, indomethacine, SOD and apocinine administration reverted the increased reactivity to phenylephrine induced by HgCl2. Results suggested that the increased phenylephrine reactivity of aortic rings induced by 6 nM HgCl2 is endothelium mediated. Such effect involves activation of the local renin-angiotensin system, vasoconstrictor protanoids release, increased release of oxygem reactive species and the reduced bioavailability of NO